SEKURITI MAKANAN DARI PERSPEKTIF SYARIAH - Ab Rahman, Asmak (Jurnal Syariah, 2009)
Food is one of the basic needs for human being. Food security is essential to the survival of human being. This research analyzed food security from the FAO definition and further redefined from Syariah perspective. Based on the definition by FAO, we found that the element of halal and tayyibah should be included in defining food security from Syariah perspective. We discovered that Islam emphasizes on food security and rank it as al-daruriyyat, which has to be fulfilled by everyone. In order to ensure food security among the society, Islam has employed numerous mechanisms such as paying zakat fitrah, dam, kaffarah, fidyah and sadaqah that are applicable to Muslims and these are considered as part of `ibadah (worship).